Twenty years of research on borderline personality disorder: a scientometric analysis of hotspots, bursts, and research trends - Liu, Yuanli; Chen, Chaomei; Zhou, Ying; Zhang, Na; Liu, Shen (Frontiers in Psychiatry, 2024)
Borderline personality disorder (BPD), a complex and severe psychiatric disorder, has become a topic of considerable interest to current researchers due to its high incidence and severity of consequences. There is a lack of a bibliometric analysis to visualize the history and developmental trends of researches in BPD. We retrieved 7919 relevant publications on the Web of Science platform and analyzed them using software CiteSpace (6.2.R4). The results showed that there has been an overall upward trend in research interest in BPD over the past two decades. Current research trends in BPD include neuroimaging, biological mechanisms, and cognitive, behavioral, and pathological studies. Recent trends have been identified as "prevention and early intervention", "non-pharmacological treatment" and "pathogenesis". The results are like a reference program that will help determine future research directions and priorities.